2000
DOI: 10.1007/bf03401783
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Placental Heme Oxygenase-1 Is Protective Against TNFα-induced Cytotoxicity and Promotes Vessel Relaxation

Abstract: Background: Pregnancy is characterized by an inflammatory-like process and this may be exacerbated in preeclampsia. The heme oxygenase (HO) enzymes generate carbon monoxide (CO) that induces blood vessel relaxation and biliverdin that acts as an endogenous antioxidant. Materials and Methods:We examined the expression and localization of HO-1 and HO-2 in normal and preeclamptic placenta using reverse transcription polymerase chain reaction (RT-PCR), RNase protection assay, immunoblotting and immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
161
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(174 citation statements)
references
References 54 publications
9
161
2
2
Order By: Relevance
“…In human pregnancies, HMOX-1 is expressed in the placenta and decidua (29,(64)(65)(66)(67)(68)(69). Placental HMOX-1 expression has been described as being significantly higher in term human placentas (66), when levels of progesterone as well as estradiol are significantly higher than in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human pregnancies, HMOX-1 is expressed in the placenta and decidua (29,(64)(65)(66)(67)(68)(69). Placental HMOX-1 expression has been described as being significantly higher in term human placentas (66), when levels of progesterone as well as estradiol are significantly higher than in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Placental HMOX-1 expression has been described as being significantly higher in term human placentas (66), when levels of progesterone as well as estradiol are significantly higher than in the first trimester. This supports the notion that HMOX-1 is modulated by progesterone during human pregnancies (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since several studies have supported the hypothesis that decreased biologically available NO is central to the pathogenesis of hypertension in women with preeclampsia (23), the inhibition of eNOS activation by intravascular sEng suggests a molecular basis for the elevated blood pressure (12). Most recently, one of the molecular mechanisms of the increases of both sFlt1 and sEng in preeclamptic women was elucidated by Cudmore et al (24); that is, heme oxygenase-1 (HO-1) is involved in negative regulation of both sFlt1 and sEng release, and it has already been reported that protein levels of HO-1 in preeclamptic placenta are decreased (25). The concentrations of sFlt1 and sEng in women with preeclampsia were positively correlated in our data and in previous reports (12,15,17), supporting the experimental results of Cudmore et al (24).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on human placentas, an induction of HOX-1 was protective against cytotoxic damage and promoted the vessel relaxation [37]. Furthermore, HOX-1 protein was significantly reduced in placentas from pregnancies complicated with pre-eclampsia, as compared with gestationally matched normal pregnancies [37].…”
Section: Glutathione In Gestational Hypertensionmentioning
confidence: 96%